Pendampingan Implementasi Digital Marketing Desa Kelumpang sebagai Sarana Pengenalan Potensi Desa Wisata - Defi Pujianto; Sri Hartati; Dian Sri Agustina; Suryanto Suryanto; Budi Kurniawan; Wisnumurti Wisnumurti; Kadarsih Kadarsih; Rusidi Rusidi; Salamudin Salamudin; Haris Saputro (Universitas Pahlawan Tuanku Tambusai, 2022)
Kelumpang Village, Ulu Ogan District, Ogan Komering Ulu Regency, has the potential for a variety of handicraft tourism, handicrafts, rafting, waterfalls and so on. The management of the village tourism sector in Kelumpang is starting to become a concern in the Ogan Komering Ulu district. This service activity focuses on promoting village tourism and community crafts in the form of creating marketing content that will be distributed through social media Facebook and Instagram. Activities carried out in the creation of marketing content. Marketing content for service activities in the form of images and videos. The method of implementing this service is assistance in the introduction of tourist villages and handicrafts from the Kelumpang village community through digital marketing that focuses on social media Facebook and Instagram. The purpose of this assistance is to increase the publication of handicraft products and tourist objects in Kelumpang Village. Through this service activity, content is produced on types of crafts and tourist objects in the form of photos that are ready to be published on social media Facebook and Instagram.